Perceptual hue, lightness, and chroma are represented in a multidimensional functional anatomical map in macaque V1. (May 2022) - Li, Ming; Ju, Niansheng; Jiang, Rundong; Liu, Fang; Jiang, Hongfei; Macknik, Stephen; Martinez-Conde, Susana; Tang, Shiming
Abstract: Humans perceive millions of colors along three dimensions of color space: hue, lightness, and chroma. A major gap in knowledge is where the brain represents these specific dimensions in cortex, and how they relate to each other. Previous studies have shown that brain areas V4 and the posterior inferotemporal cortex (PIT) are central to computing color dimensions. To determine the contribution of V1 to setting up these downstream processing mechanisms, we studied cortical color responses in macaques—who share color vision mechanisms with humans. We used two-photon calcium imaging at both meso- and micro-scales and found that hue and lightness are laid out in orthogonal directions on the cortical map, with chroma represented by the strength of neuronal responses, as previously shown in PIT. These findings suggest that the earliest cortical stages of vision determine the three primary dimensions of human color perception. Highlights: Hue representation in V1 forms pinwheel-like and linear zone patterns. Achromatic and chromatic lightness representation in V1 forms linear zone patterns. Chroma is represented in V1 by the strength of cortical responses. Representations of hue and lightness in V1 are orthogonal to each other. Perceptual colors dimensions are well represented in V1 at both cellular and brain structure level.